Departmental Workload and Job Satisfaction of Indonesian Nurses in Saudi Arabia: A Cross Sectional Study - Fahruddin, Akhir; Setyorini, Dwi; Saodah, Siti (Universitas Muhammadiyah Surakarta, 2024)
Indonesian foreign nurses working in Saudi Arabia have not been surveyed regarding workload and job satisfaction in the healthcare setting. Understanding the workload at hospital that influences job satisfaction provides an overview of the nurse’s existence at work. This study aimed to determine the prevalence of workload, and job satisfaction of Indonesian nurses in Saudi Arabia. A cross sectional study using self- administered questionnaire by Nasa Task Load Index (NASA-TLX) was used to analyze the workload, and the Minnesota Satisfaction Questionnaire (MSQ) for the satisfaction. Data were analyzed using descriptive methods and univariate statistics by SPSS version 26. A total of 132 nurses participated in this research. Five departments, including intensive care unit (ICU), emergency department (ER), operating room (OR), hemodialysis (HD), and ward department (WD) reported high workload levels (61-80 points). Job satisfaction in five departments was neutral category, while the ward department showed dissatisfied category. The analysis of nurses' characteristics revealed that the majority were aged 31-40 years old (46.2%), length of work was 1-5 years (54.5%), and worked in the outpatient department (42.4%). The study suggests that healthcare management and policymakers should implement programs to improve job satisfaction and reduce workload, especially for foreign nurses working in critical areas, including the five departments mentioned.